Analisis Supply Chain Management (SCM) Perdagangan Ikan Hiun di PPS Lampulo Banda Aceh - Egi Mufadhdhal; Lukman Hakim; Agus Nugroho (Fakultas Pertanian, Universitas Syiah Kuala, 2022)
This study aims to identify the structure of the Shark supply chain pattern and analyze the additional income margins of fishermen on the shark trade at PPS Lampulo, Banda Aceh. The population in this study were all fishermen and all traders who carried out shark trading activities in the area around PPS Lampulo, Banda Aceh city. The number of samples taken in this study were 13 respondents. The respondents are 5 fishermen and 8 traders who are around the PPS Lampulo area, Banda Aceh city. Sampling using snowball sampling technique. The research method used to support the perfection of the research to be carried out, the research uses qualitative analysis methods. The results showed that the supply chain model for sharks at PPS Lampulo is fishermen who rent boats, who carry out shark fishing activities at sea, wholesalers or Toke who buy sharks to be distributed / resold, or to be processed and then sold in product form. processed. Retailers, consisting of traveling merchants, who buy Sharks from wholesalers on a retail basis. Consumers, namely final buyers who buy Sharks for consumption, either inside or outside. Fishermen do not deal directly with the final consumer in distributing their products, but through traders/bench toke who are direct consumers for fishermen. Fishermen are the main suppliers who supply sharks to wholesalers/toke. Fishermen supply their catch to contractors through PPS Lampulo. The wholesaler/toke must come to PPS to buy/order sharks and must get a price agreement with the fishermen.